Fenotipagem para estudos de estudos de tolerância à deficiência hídrica em eucalipto - Mendes, Hélio Sandoval Junqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The eucalyptus culture has great importance for the Brazilian forestry sector, being an excellent timber option for many purposes. Over recent years, the eucalyptus cultivation has expanded to regions with high levels of water deficit, imposing a new challenge for breeders and foresters that is recommendation of drought resistant genotypes. Thus, this work aim to evaluate the imposition of different ways of water stress on eucalypt, provided by types of pots and irrigation schemes combination, in order to advance in phenotyping methods in drought tolerance studies. Therefore, changes in Eucalyptus clones seeding physiological, biochemical and growth under different water availability conditions were studied. Three experiments were conducted: the first was conducted in cylindrical recipients of PVC under two irrigation regimes (R1 - alternate day and R2 - interruption of watering until visible wilting occurred) and three hybrids (H1 and H2 - Eucalyptus urophylla x E. tereticornis and H3 - hybrid E. urophylla x E. brassiana). Were evaluated in this experiment the following aspects: a) growth: height, stem diameter, number of leaves, leaf area, dry mass of leaves of stem + branches, root, aerial part, total and root/aerial part ratio; b) physiological: net assimilation rates, stomatal conductance, transpiration, water potential, membrane system damage, relative water content; c) biochemical: reducer and total soluble sugars content in leaves and roots. In the second experiment was monitored the survival of five clones of eucalypt (four hybrids of Eucalyptus grandis x E. urophylla - C1, C2, C3 and C5) and one clone of E. urophylla (C4): after watering interruption, in different sizes pots (3,6 L, 8 L, 25 L and 100 L). The gas exchange was evaluated and the hybrids death time delay counted. The third experiment was performed in two sizes pots (8 and 25 L), two irrigation schemes (the same as in the first experiment - R1 and R2) and ...

A cultura do eucalipto é de grande importância para o setor florestal brasileiro, constituindo-se numa excelente opção madeireira para diversos usos. Nos últimos anos, o cultivo do eucalipto tem-se expandido para regiões com altos índices de deficiência hídrica, impondo-se um novo desafio para melhoristas e silvicultores que é a recomendação de genótipos tolerantes à seca. Com isto, objetivou-se neste trabalho avaliar diferentes formas de imposição de deficiência hídrica em eucalipto, proporcionadas pela combinação de tipos de vasos e regimes de irrigação, buscando-se avançar nos métodos de fenotipagem em estudos de tolerância à seca. Para estudar as alterações fisiológicas, bioquímicas e no crescimento de mudas de clones de Eucalyptus submetidos a diferentes condições de disponibilidade hídrica, foram conduzidos três experimentos. No primeiro experimento em recipientes cilíndricos de PVC sob dois regimes de irrigação (R1 - irrigação em dias alternados e R2 - irrigação suspensa até o aparecimento de sintomas iniciais de murcha) e três híbridos de eucalipto (H1 e H2 - híbridos de Eucalyptus urophylla X E. tereticornis e H3 - hibrido de E. urophylla X E. brassiana) foram avaliadas as seguintes características: a) crescimento: altura, diâmetro do coleto, número de folhas, área foliar, matéria seca de folhas, de caule + ramos, de raízes, da parte aérea e total, relação raiz/parte aérea; b) fisiológicas: taxas de assimilação líquida, condutância estomática, transpiração, potencial hídrico, danos ao sistema de membranas, conteúdo relativo de água; c) bioquímicas: teores de açúcares redutores e açúcares solúveis totais em folhas e raízes. No segundo experimento acompanhou-se a sobrevivência de cinco clones de eucalipto, sendo quatro clones de hibridos de Eucalyptus grandis x E. urophylla (G1, G2, G3 e G5) e um de E. urophylla (G4), após a suspensão da irrigação, em ...
Keywords: Eucalipto; Açucar; Irrigação com déficit hídrico; Vasos; Tolerancia; Deficit irrigation